2014
DOI: 10.1002/2014gl061127
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a strongly negative surface potential at Saturn's moon Hyperion

Abstract: On 26 September 2005, Cassini conducted its only close targeted flyby of Saturn's small, irregularly shaped moon Hyperion. Approximately 6 min before the closest approach, the electron spectrometer (ELS), part of the Cassini Plasma Spectrometer (CAPS) detected a field-aligned electron population originating from the direction of the moon's surface. Plasma wave activity detected by the Radio and Plasma Wave instrument suggests electron beam activity. A dropout in energetic electrons was observed by both CAPS-EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(68 reference statements)
2
10
0
Order By: Relevance
“…• Previous theoretical studies have predicted large negative surface potentials at Rhea up to several hundred volts [Roussos et al, 2010;Nordheim et al, 2014] and observations during the Rhea R2 flyby appear to support this [Santolík et al, 2011]. However, for surface potentials to explain the observed energy discrepancy, a negative surface potential of 500V would have to occur uniformly over a large region of Rhea's surface.…”
Section: Velocity Space Analysismentioning
confidence: 90%
“…• Previous theoretical studies have predicted large negative surface potentials at Rhea up to several hundred volts [Roussos et al, 2010;Nordheim et al, 2014] and observations during the Rhea R2 flyby appear to support this [Santolík et al, 2011]. However, for surface potentials to explain the observed energy discrepancy, a negative surface potential of 500V would have to occur uniformly over a large region of Rhea's surface.…”
Section: Velocity Space Analysismentioning
confidence: 90%
“…De and Criswell (1977) and Lee (1996) used the value of 3.0×10 5 V/m as the electric field strength across lunar terminator. As on the Moon, it is observed that Hyperion has intense electric fields at its terminator (Nordheim et al 2014). An experimental study, setting a plane with a potential of 10 V adjacent to a plane with a potential of 0 V owing to differential UV charging, showed that strong electric fields, ~1 kV/m, can be generated across the boundary (Wang et al 2007).…”
Section: Generation Of An Intense Electric Field On Particle Surfaces...mentioning
confidence: 99%
“…One finding has been that of long-term reconnection in the tail (Arridge et al 2016), confirmation of the Vasyliunas cycle, plasmoids in the tail taking products from Enceladus away from the Saturn system (Hill et al 2008, Jackman et al 2014, observation of a "polar wind" like Earth's (Felici et al 2016), new radiation belts unknown before Cassini arrived (Krimigis et al 2005), and charging of the surface at Hyperion (Nordheim et al 2014) and other moons.…”
Section: Magnetospherementioning
confidence: 99%